Lethal complication of a rare cardiac tumor - Siegel, Sonja; Claus, L.; Kamphausen, T.; Feld, Katharina (Forensic science, medicine, and pathology, 2023)
Cardiac tumors, especially malignant ones, are rare and diagnosis is challenging since symptoms manifest late and are often non-specific. Achieving a histological diagnosis prior to resection is also difficult because biopsies often fail to yield conclusive results. Due to the low frequency, no standard treatment protocol exists and the prognosis is poor. We present a case of a cardiac sarcoma, which was found during an autopsy performed with regard to medical malpractice, because the patient died due to a medical intervention. To report cases like this is important to gain more knowledge about possible complications regarding rare diseases.
Online veröffentlicht: 16. September 2023
Gesehen am 28.11.2023